Association between job role and coronavirus disease 2019 (COVID-19) among healthcare personnel, Iowa, 2021. Issue 1 (1st December 2022) - Kobayashi, Takaaki; Trannel, Alexandra; Heinemann, John; Marra, Alexandre R.; Etienne, William; Abosi, Oluchi J.; Holley, Stephanie; Dains, Angelique; Jenn, Kyle E.; Meacham, Holly; Schuessler, Barbara A.; Wendt, Linder; et al.
Abstract: We describe the association between job roles and coronavirus disease 2019 (COVID-19) among healthcare personnel. A wide range of hazard ratios were observed across job roles. Medical assistants had higher hazard ratios than nurses, while attending physicians, food service workers, laboratory technicians, pharmacists, residents and fellows, and temporary workers had lower hazard ratios.